The impact of temperature on cotton yield and production in Xinjiang, China - Yongyan Zhao; Yumeng Zhu; Shouli Feng; Ting Zhao; Luyao Wang; Zhihong Zheng; Nijiang Ai; Xueying Guan (npj Sustainable Agriculture)
Abstract Cotton production in Xinjiang is crucial to China’s economy, but the region’s cold climate poses challenges to cultivation. This study analyzes temperature data from 33 meteorological stations in Xinjiang (1981–2020) alongside cotton yield data to assess cold damage during key cotton growth stages. A comparison is made with cotton-producing counties in the U.S. southwest (Texas, Kansas, Oklahoma). Results show that Xinjiang has a shorter frost-free period (140–210 days) compared to the U.S. (235–300 days). The Pearson correlation coefficient indicates that spring cold damage (SpCD) during emergence stage significantly impacts yield. SpCD lasts 5–10 days in NXJ, 3–7 days in SXJ, and 3–4 days in the U.S. Severe cold damage, notably in 1996 and 2010, led to a 40% yield decline. To mitigate cold damage, breeding cold-tolerant cotton varieties and developing innovative cultivation technologies are critical for sustaining cotton production in Xinjiang.